All solid state battery
By introducing carbon particles with an average surface spacing d002 less than 0.342nm into the positive and negative electrode material layers of all solid state batteries, the problem of high internal resistance is solved, and the high energy density and high charge/discharge capability of the battery are achieved.
Patent Information
- Application Number
- JP2022505001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-06
- Filing Date
- 2021-01-06
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-01-06
AI Technical Summary
All existing solid-state batteries have high internal resistance, resulting in smaller discharge capacity of the battery, making it difficult to meet the needs of high energy density and high charge/discharge capabilities.
Carbon particles with an average surface spacing d002 less than 0.342 nm are introduced into the positive and negative electrode material layer to improve the electronic conductivity of the electrode and reduce the internal resistance of the battery by optimizing the shape and distribution of the carbon particles.
By introducing carbon particles with high crystalline and high conductivity, the internal resistance of all solid-state batteries is significantly reduced, and the discharge capacity and energy density of the batteries are improved.
Smart Images

Figure 0007660097000005 
Figure 0007660097000001 
Figure 0007660097000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state battery. This application claims priority based on Japanese Patent Application No. 2020-39384, filed on March 6, 2020, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, with the development of portable devices such as personal computers and mobile phones, the demand for batteries as their power sources has increased significantly. In batteries used for such purposes, liquid electrolytes (electrolytic solutions) such as organic solvents have traditionally been used as a medium for transferring ions. In batteries using such electrolyte solutions, problems such as leakage of the electrolyte solution may occur.
[0003] In order to solve such problems, development of all-solid-state batteries is underway, in which a solid electrolyte is used instead of a liquid electrolyte and all other elements are made of solids. Since the electrolyte of such all-solid-state batteries is solid, there is no need to worry about leakage or depletion of the electrolyte, and problems such as deterioration of battery performance due to corrosion are unlikely to occur. In particular, all-solid-state batteries have been actively researched in various fields as secondary batteries that can easily achieve high charge / discharge capacity and energy density.
[0004] However, all-solid-state batteries using solid electrolytes as electrolytes still have a problem that the discharge capacity is generally smaller than that of batteries using liquid electrolytes. Therefore, Li3V2(PO4)3 (hereinafter referred to as LVP323), a Nasicon-type phosphoric acid-based active material, has multiple redox potentials (3.8V, 1.8V), and in a symmetrical electrode battery using this for the positive and negative electrodes, a 2V-class all-solid-state battery can be obtained. However, this LVP323 has a lower electronic conductivity than when LiCoO2 is used as the active material, and there is a problem that the internal resistance of the battery increases and the discharge capacity decreases. In order to improve this electronic conductivity, the electrode layer or collector layer contains multiple conductive materials oriented almost perpendicular to the stacking direction, thereby increasing the electronic conductivity in the surface direction within the electrode layer or collector layer. In particular, it has been suggested that a collector that involves sintering should contain carbon due to concerns about metal oxidation (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5804208 Summary of the Invention [Problem to be solved by the invention]
[0006] However, there is a demand for further reduction in the internal resistance of all-solid-state batteries. Therefore, even the all-solid-state battery disclosed in Patent Document 1 still has room for improvement in terms of discharge capacity.
[0007] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide an all-solid-state battery having a further reduced internal resistance. [Means for solving the problem]
[0008] As a result of intensive research into achieving the above object, the inventors have found that in an all-solid-state battery having a solid electrolyte layer between a pair of electrodes, by using carbon particles having an average interplanar spacing d002 of less than 0.342 (nm) in the positive electrode active material layer and the negative electrode active material layer, the internal resistance of the battery can be reduced by adding a small amount of carbon particles, and have thus completed the present invention.
[0009] That is, according to the present invention, the following all-solid-state battery is provided.
[0010] An all-solid-state battery according to one embodiment of the present invention includes a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer, a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer, and a solid electrolyte layer including a solid electrolyte, wherein the positive electrode active material layer and the negative electrode active material layer contain carbon particles having an average interplanar spacing d002 smaller than 0.342 (nm).
[0011] According to this configuration, the internal resistance of the all-solid-state battery can be reduced. Carbon particles with an average interplanar spacing d002 smaller than 0.342 (nm) have good crystallinity as a graphite structure, and have small periodic disorder, which means that they have high thermal stability and can be easily left in the electrode even when a process involving post-heat treatment such as sintering is used. Therefore, high electronic conductivity can be obtained with a small amount of addition, and a high-density electrode can be realized. Furthermore, these carbon particles have high crystallinity, so that the electronic conductivity is high. Therefore, by mixing these carbon particles with an active material to form an electrode, the electronic conductivity of the electrode can be increased with a small amount of addition, and the internal resistance of the all-solid-state battery can be reduced. Furthermore, a small amount of voids may be generated near the carbon particles due to evaporation of carbon during heat treatment or the like.
[0012] In the all-solid-state battery according to one embodiment of the present invention, the carbon particles have a long side a and a short side b such that the ratio of the long side a to the short side b is 1.0.
[0013] According to this configuration, the carbon particles having small shape anisotropy can be densely packed together with the active material particles in the active material, and the contact area with the active material increases, facilitating electron transfer, which increases the electronic conductivity in the electrode and reduces the internal resistance of the all-solid-state battery.
[0014] In the all-solid-state battery according to one embodiment of the present invention, the carbon particles may have a particle size distribution in which D10 is 0.1 μm or more and D90 is 5.0 μm or less.
[0015] According to this configuration, the carbon particles can be brought into contact with the amount of active material without excess or deficiency, and further, contact can be made without generating voids between the carbon particles and the active material, so that electrons can be exchanged smoothly and the internal resistance of the all-solid-state battery can be reduced. Also, when fine particles with D10 of less than 0.1 μm are included, the carbon particles easily evaporate during processes such as heat treatment, and sufficient effects cannot be obtained.
[0016] In the all-solid-state battery according to one aspect of the present invention, the positive electrode active material layer and the negative electrode active material layer may each contain 0.5 (wt %) or more and 15.0 (wt %) or less of the carbon particles.
[0017] With such a carbon particle content, the carbon particles are in sufficient contact with each other, making it possible to increase the electronic conductivity of the electrode and suppress a substantial decrease in the amount of active material. As a result, the internal resistance of the all-solid-state battery can be reduced while a high capacity can be obtained. Effect of the Invention
[0018] According to the present invention, it is possible to provide an all-solid-state battery with reduced internal resistance. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view of an all-solid-state battery of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations are omitted. In addition, the dimensional ratios of the drawings are not limited to those shown. The drawings used in the following description may be enlarged to show the characteristic parts of the present invention for the sake of convenience in order to make the features of the present invention easier to understand. Therefore, the dimensional ratios of each component described in the drawings may differ from the actual ones. The materials, dimensions, shapes, etc. exemplified in the following description are only examples, and the present invention is not limited to them. The present invention can be implemented by appropriately changing the present invention within the scope of its effects without changing the gist of the present invention. For example, the configurations described in different embodiments and the configurations described in the examples can be implemented by appropriately combining them. In this embodiment, one direction of the stacking direction may be referred to as the upward direction and the downward direction, but the upward and downward directions in this case do not necessarily coincide with the direction in which gravity is applied.
[0021] (All-solid-state battery) Fig. 1 is a schematic cross-sectional view showing a structure for explaining the concept of an all-solid-state battery 10 of this embodiment. As shown in Fig. 1, the all-solid-state battery 10 of this embodiment has at least one positive electrode layer 1, at least one negative electrode layer 2, and a solid electrolyte layer 3 at least a part of which is sandwiched between the positive electrode layer 1 and the negative electrode layer 2. The positive electrode layer 1, the solid electrolyte layer 3, and the negative electrode layer 2 are laminated in this order to form a laminate 4. The positive electrode layers 1 are each connected to a terminal electrode 5 disposed on one end side, and the negative electrode layers 2 are each connected to a terminal electrode 6 disposed on the other end side.
[0022] The positive electrode layer 1 is an example of a first electrode layer, and the negative electrode layer 2 is an example of a second electrode layer. One of the first electrode layer and the second electrode layer functions as a positive electrode, and the other functions as a negative electrode. The positive and negative polarities of the electrode layers change depending on which polarity is connected to the terminal electrodes 5 and 6.
[0023] The positive electrode layer 1 has a positive electrode collector layer 1A and a positive electrode active material layer 1B formed on one or both sides of the positive electrode collector layer 1A. The surface of the positive electrode collector layer 1A on which the opposing negative electrode layer 2 is not present may not have the positive electrode active material layer 1B. The negative electrode layer 2 has a negative electrode collector layer 2A and a negative electrode active material layer 2B formed on one or both sides of the negative electrode collector layer 2A. The surface of the negative electrode collector layer 2A on which the opposing positive electrode layer 1 is not present may not have the negative electrode active material layer 2B. For example, the positive electrode layer 1 or the negative electrode layer 2 located in the uppermost layer or the lowermost layer of the laminate 4 may not have the positive electrode active material layer 1B or the negative electrode active material layer 2B on one side.
[0024] The all-solid-state battery 10 according to this embodiment is an all-solid-state battery having a solid electrolyte layer 3 between a pair of electrode layers, and the positive electrode active material layer 1B and the negative electrode active material layer 2B included in the pair of electrode layers contain carbon particles having an average interplanar spacing d002 of less than 0.342 (nm).
[0025] Carbon particles with an average interplanar spacing d002 smaller than 0.342 (nm) have good crystallinity as a graphite structure and small periodic disorder, resulting in high electronic conductivity. By mixing these carbon particles with an active material to form an electrode, the electrode has high thermal stability and can be easily left in the electrode even when a process involving post-heat treatment such as sintering is used. Therefore, high electronic conductivity can be obtained with a small amount of addition, making it possible to realize a high-density electrode. Furthermore, these carbon particles have high crystallinity and high electronic conductivity. Therefore, by mixing these carbon particles with an active material to form an electrode, the electronic conductivity of the electrode can be increased with a small amount of addition, and the internal resistance of the all-solid-state battery can be reduced. Furthermore, a small amount of voids may be generated near each carbon particle due to evaporation of carbon during heat treatment or the like.
[0026] The interplanar spacing d002 of the carbon particles of this embodiment can be calculated from the peak angle of the plane index (002) using, for example, an X-ray diffraction device (device name: Xpert-N, manufactured by Malvem-Panalytical) according to 2d·sinθ=n·λ (where d is the interplanar spacing, θ is the measurement angle, n is an arbitrary integer, and λ is the wavelength of the X-rays used).
[0027] In the positive electrode active material layer 1B and the negative electrode active material layer 2B of the all-solid-state battery 10 according to this embodiment, when the long side of the particle is a and the short side is b, the ratio of the long side to the short side is 1.0
[0028] According to this configuration, the carbon particles having small shape anisotropy can be densely packed together with the active material particles in the active material, and the contact area with the active material increases, facilitating electron transfer, thereby increasing the electronic conductivity in the electrode and decreasing the internal resistance of the all-solid-state battery 10.
[0029] The positive electrode active material layer 1B and the negative electrode active material layer 2B of the all-solid-state battery 10 according to this embodiment preferably further contain carbon particles having a particle size distribution of D10 of 0.1 μm or more and D90 of 5.0 μm or less. D10 is the diameter of the particles that is 10% by volume of the cumulative volume in the distribution curve obtained by measuring the particle size distribution of the circle-equivalent diameter calculated based on the area data of the carbon particles. D90 is the diameter of the particles that is 90% by volume of the cumulative volume in the distribution curve obtained by measuring the particle size distribution.
[0030] According to this configuration, the carbon particles can be brought into contact with the active material without excess or deficiency, and the contact can be made without creating voids between the active material, which facilitates the exchange of electrons and reduces the internal resistance of the all-solid-state battery. In addition, when fine particles with D10 of less than 0.1 μm are not included, the evaporation of carbon particles during processes such as heat treatment is suppressed, and sufficient effects are guaranteed.
[0031] The positive electrode active material layer 1B and the negative electrode active material layer 2B of the all-solid-state battery 10 according to this embodiment preferably contain carbon particles in an amount of 0.5 (wt %) or more and 15.0 (wt %) or less, respectively.
[0032] With such a carbon particle content, the carbon particles are in sufficient contact with each other, which increases the electronic conductivity of the electrode, and also makes it possible to suppress a substantial decrease in the amount of active material. As a result, the internal resistance of the all-solid-state battery 10 can be reduced while a high capacity can be obtained.
[0033] (carbon particles) The carbon particles of this embodiment may be either artificially synthesized or natural minerals, as long as they have an average interplanar spacing d002 of less than 0.342 (nm).
[0034] (solid electrolyte) At least a portion of the solid electrolyte layer 3 is sandwiched between the positive electrode layer 1 and the negative electrode layer 2. As shown in FIG. 1, at least a portion of the solid electrolyte layer 3 may be located in the in-plane direction of the positive electrode layer 1 and the negative electrode layer 2. For example, a material having ionic conductivity and negligibly small electronic conductivity is used for the solid electrolyte in the solid electrolyte layer 3. Examples of the solid electrolyte include lithium halides, lithium nitrides, lithium oxyacid salts, and derivatives thereof. In addition, Li-PO-based compounds such as lithium phosphate (Li3PO4), and LIPON (LiPO 4-x N x ), Li-Si-O compounds such as Li4SiO4, Li-P-Si-O compounds, Li-VSi-O compounds, and perovskite-structured La 0.51 Li 0.35 TiO 2.94 , La 0.55 Li 0.35 TiO3, Li 3x La 2 / 3-x Examples of the compounds include perovskite compounds such as TiO3, and compounds having a garnet structure containing Li, La, and Zr. In particular, it is preferable to include a compound having a Nasicon structure. The composition of the compound having the Nasicon structure is Li x M y It is represented by (PO4)3 (x=1-2, y=1-2, M=Ti, Ge, Al, Ga, Zr), and some of the P may be replaced by B, Si, etc. Examples of compounds having a Nasicon structure include Li 1.3 Al0.3 Ti 1.7 (PO4)3 and Li 1.5 Al 0.5 Ge 1.5 (PO4)3 is an example.
[0035] (Negative electrode active material) The negative electrode active material layer 2B contains a negative electrode active material. 12 Alternatively, an oxide of at least one element selected from the group consisting of Ti, Nb, W, Si, Sn, Cr, Fe, and Mo, or a phosphorus-containing compound such as Li3V2(PO4)3 or LiFePO4 may be used.
[0036] (Cathode active material) The positive electrode active material layer 1B contains a positive electrode active material. The positive electrode active material is LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, etc., layered compounds, LiMn2O4, LiNi 0.5 Mn 1.5 Spinel materials such as O4, phosphorus-containing compounds such as Li3V2(PO4)3 and LiFePO4, etc. may also be used. The effect of the present invention can be achieved as long as at least one of the positive electrode active material and the negative electrode active material contains the carbon material of the present invention.
[0037] There is no clear distinction between the materials constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B, and the potentials of two types of compounds, the compound in the positive electrode active material layer 1B and the compound in the negative electrode active material layer 2B, are compared, and the compound showing a more noble potential can be used as the positive electrode active material, and the compound showing a more base potential can be used as the negative electrode active material. In addition, the active materials constituting the positive electrode active material layer 1B and the negative electrode active material layer 2B may be the same material, so long as they have both a lithium ion release function and a lithium ion absorption function. By using the same material for the active materials constituting the positive electrode active material layer 1B and the negative electrode active material layer 2B, a non-polar all-solid-state battery is obtained, and there is no need to specify the direction when mounting on a circuit board, which makes it easier to mount.
[0038] (current collector) The materials constituting the positive electrode collector layer 1A and the negative electrode collector layer 2A are preferably materials with high electrical conductivity, such as silver, palladium, gold, platinum, aluminum, copper, nickel, etc. Copper is particularly preferred because it does not react easily with lithium titanium aluminum phosphate and is effective in reducing the internal resistance of the all-solid-state battery. The materials constituting the collector layers may be the same for the positive electrode layer and the negative electrode layer, or may be different.
[0039] Moreover, the positive electrode current collector layer 1A and the negative electrode current collector layer 2A of the all-solid-state battery in this embodiment preferably contain a positive electrode active material and a negative electrode active material, respectively.
[0040] It is desirable for the positive electrode current collector layer 1A and the negative electrode current collector layer 2A to contain the positive electrode active material 1B and the negative electrode active material 2B, respectively, because this improves the adhesion between the positive electrode current collector layer 1A and the positive electrode active material layer 1B, and between the negative electrode current collector layer 2A and the negative electrode active material layer 2B.
[0041] (terminal electrode) The terminal electrodes 5 and 6 are formed in contact with the side surfaces of the sintered body. The terminal electrodes 5 and 6 are connected to external terminals and are responsible for giving and receiving electrons to and from the sintered body.
[0042] It is preferable to use a material with high electrical conductivity for the terminal electrodes 5 and 6. For example, silver, gold, platinum, aluminum, copper, tin, nickel, gallium, indium, and alloys thereof can be used.
[0043] (Manufacturing method of all-solid-state batteries) In the method for producing the all-solid-state battery of this embodiment, first, the materials for the positive electrode collector layer, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, and the negative electrode collector layer are made into a paste, which is then coated and dried to produce a green sheet (first step). Next, the green sheets are stacked to produce a laminate (second step). Next, the produced laminate is fired simultaneously to produce the battery (third step).
[0044] (1st step) First, a positive electrode active material, a negative electrode active material, and a carbon material are prepared. At this time, when the active material contains a compound of two or more elements, a mixed material in which the compounds of the respective elements are mixed may be prepared. Also, when a solid electrolyte is mixed into the active material, a mixed material may be prepared.
[0045] The method for producing the paste for the positive electrode active material layer and the negative electrode active material layer is not particularly limited, but for example, the positive electrode active material, the negative electrode active material, and a carbon material can be mixed in a vehicle to obtain a paste. Here, the vehicle is a general term for a medium in a liquid phase. The vehicle includes a solvent and a binder. By this method, a paste for the positive electrode collector layer, a paste for the positive electrode active material layer, a paste for the solid electrolyte layer, a paste for the negative electrode active material layer, and a paste for the negative electrode collector layer are prepared.
[0046] The prepared paste is applied to a substrate such as PET in a desired order, and after drying as necessary, the substrate is peeled off to prepare a green sheet. The method of applying the paste is not particularly limited, and known methods such as screen printing, application, transfer, doctor blade, etc. can be used.
[0047] (2nd process) The green sheets thus produced are stacked in a desired order and number of layers, and aligned, cut, etc., as necessary, to produce a laminate. When producing a parallel or series-parallel battery, it is preferable to align and stack the green sheets so that the end faces of the positive electrode layer and the negative electrode layer do not coincide with each other.
[0048] When preparing the laminate, an active material layer unit described below may be prepared and then the laminate may be prepared.
[0049] The method is as follows: first, a paste for a solid electrolyte layer is formed in a sheet shape on a PET film by a doctor blade method, a solid electrolyte sheet is obtained, and then a paste for a positive electrode active material layer is printed on the solid electrolyte sheet by screen printing and dried. Next, a paste for a positive electrode current collector layer is printed on the solid electrolyte sheet by screen printing and dried. A paste for a positive electrode active material layer is printed again on the solid electrolyte sheet by screen printing, dried, and then the PET film is peeled off to obtain a positive electrode active material layer unit. In this way, a positive electrode active material layer unit is obtained in which a paste for a positive electrode active material layer, a paste for a positive electrode current collector layer, and a paste for a positive electrode active material layer are formed in this order on a sheet for a solid electrolyte layer. A negative electrode active material layer unit is also produced in the same procedure, and a negative electrode active material layer unit is obtained in which a paste for a negative electrode active material layer, a paste for a negative electrode current collector layer, and a paste for a negative electrode active material layer are formed in this order on a solid electrolyte sheet.
[0050] One positive electrode active material layer unit and one negative electrode active material layer unit are stacked with a solid electrolyte sheet between them. At this time, the units are stacked with a shift so that the paste for the positive electrode current collector layer of the first positive electrode active material layer unit extends only to one end face, and the paste for the negative electrode current collector layer of the second negative electrode active material layer unit extends only to the other face. Solid electrolyte sheets of a predetermined thickness are further stacked on both sides of the stacked units to produce a laminate.
[0051] The produced laminate is pressure-bonded together while heating, and the heating temperature is, for example, 40 to 95°C.
[0052] (3rd step) The pressure-bonded laminate is heated and sintered, for example, at 600° C. to 1100° C. in a nitrogen atmosphere. The sintering time is, for example, 0.1 to 3 hours. The laminate is completed by this sintering.
[0053] Furthermore, in order to efficiently extract current from the sintered body, a terminal electrode can be provided. The terminal electrode is connected to one end of the positive electrode layer extending to one side of the sintered body and one end of the negative electrode layer extending to one side of the sintered body, respectively. Thus, a pair of terminal electrodes is formed so as to sandwich one side of the sintered body. Examples of methods for forming the terminal electrodes include sputtering, screen printing, and dip coating. In the screen printing and dip coating methods, a paste for terminal electrodes containing metal powder, resin, and solvent is prepared and formed into a terminal electrode. Next, a baking process is performed to remove the solvent, and a plating process for protection and mounting is performed on the surface of the terminal electrode. On the other hand, in the sputtering method, a protective layer and a layer for mounting can be formed on the terminal electrode, so that the baking process and the plating process are not necessary. By going through the above-mentioned steps, it is possible to manufacture an all-solid-state battery.
[0054] The present invention is not necessarily limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention. In other words, the configurations and combinations thereof in the above-described embodiment are merely examples, and additions, omissions, substitutions, and other modifications can be made to the configurations without departing from the spirit of the present invention. EXAMPLES
[0055] [Examples 1 to 4] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0056] (Preparation of positive electrode active material) In order to demonstrate the effect of this embodiment, Li3V2(PO4)3 was used as the active material. LiPO3 and V2O3 were used as starting materials, and after weighing the starting materials, they were mixed and pulverized in ethanol for 16 hours using a ball mill (120 rpm / zirconia balls). The mixed powder of the starting materials was separated from the balls and ethanol, dried, and then calcined using a magnesia crucible. Calcination was performed in a reducing atmosphere at 950°C for 2 hours, and then the calcined powder was treated in ethanol for 16 hours in a ball mill (120 rpm / zirconia balls) for pulverization. The pulverized powder was separated from the balls and ethanol and dried, and Li3V2(PO4)3 powder was obtained.
[0057] (Preparation of negative electrode active material) As the negative electrode active material, the same powder as that of the positive electrode active material was used.
[0058] (Preparation of solid electrolyte) The solid electrolyte was prepared as follows: 1.3 Al 0.3 Ti 1.7 (PO4)3 was used. Li2CO3, Al2O3, TiO2, and NH4H2PO4 were used as starting materials, and wet-mixed in a ball mill for 16 hours using ethanol as a solvent. The mixed powder of the starting materials was separated from the balls and ethanol, dried, and then calcined in an alumina crucible at 850°C in air for 2 hours. The calcined powder was then processed in a ball mill (120 rpm / zirconia balls) in ethanol for 16 hours for pulverization. The pulverized powder was separated from the balls and ethanol, and dried to obtain a powder.
[0059] (Mixing active material and carbon material) In order to demonstrate the effect of this embodiment, carbon materials having D10 of 0.25 μm, D90 of 4.5 μm, a / b of 3, and average interplanar spacing d002 of 0.3354, 0.3365, 0.3380, and 0.3410 (nm) were used as Examples 1 to 4. The active material used was Li3V2(PO4)3 described above. First, the carbon materials having the respective average interplanar spacings were weighed out to be 10.7, 11.3, 12.6, and 13.5 (wt%) relative to Li3V2(PO4)3, and mixed in an organic solvent using a ball mill. The powder was separated from the balls and organic solvent, dried, and a mixed powder of the carbon material and Li3V2(PO4)3 was obtained. Here, the carbon material added to Li3V2(PO4)3 is described in the table as the amount of added carbon material.
[0060] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive and negative electrode active material layers was prepared by adding 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent to 100 parts of a mixed powder of the above carbon material and Li3V2(PO4)3, and kneading and dispersing the mixture using a triple roll mill to prepare a paste for the active material layers that would become the positive and negative electrodes.
[0061] (Preparation of paste for solid electrolyte layer) The solid electrolyte is the above-mentioned Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was used. 100 parts of this powder were mixed with 100 parts of ethanol and 200 parts of toluene as solvents in a ball mill and wet-mixed. Then, 16 parts of polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare a paste for the solid electrolyte layer.
[0062] (Preparation of sheets for solid electrolyte layer) This paste for the solid electrolyte layer was formed into a sheet using a doctor blade method on a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.
[0063] (Preparation of Positive Electrode Current Collector Layer Paste and Negative Electrode Current Collector Layer Paste) Cu powder and Li3V2(PO4)3 powder were mixed in a weight ratio of 100:9, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added, and the mixture was mixed and dispersed using a triple roll to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.
[0064] (Preparation of terminal electrode paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting terminal electrode paste.
[0065] (Preparation of active material layer unit) On the above-mentioned sheet for the solid electrolyte layer, the paste for the electrode collector layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes. On top of that, the paste for the positive electrode active material layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes to form a positive electrode layer unit. On the other hand, on the sheet for the solid electrolyte layer, the paste for the negative electrode active material layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes, and then the paste for the electrode collector layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes to form a negative electrode layer unit. Then, the PET film was peeled off.
[0066] (Preparation of Laminate) A stack was obtained by stacking the positive electrode layer unit, the negative electrode layer unit, and the solid electrolyte layer sheet in the order of the solid electrolyte layer, the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, the negative electrode current collector layer, and the solid electrolyte layer. At this time, each unit was stacked with a shift so that the positive electrode current collector layer of the positive electrode layer unit extended only to one end surface, and the negative electrode current collector layer of the negative electrode active material layer unit extended only to the other end surface. Then, this was molded by thermocompression bonding, and cut to produce a stack.
[0067] (Preparation of sintered body) The obtained laminate was debindered and then co-fired to obtain a sintered body. For debindering, the temperature was raised to 700°C at a rate of 50°C / hour in nitrogen and held at that temperature for 10 hours, and for co-firing, the temperature was raised to 850°C at a rate of 200°C / hour in nitrogen and held at that temperature for 1 hour, and then naturally cooled after firing. It was also confirmed that the residual carbon content in the electrode active material layer region of the obtained sintered body was approximately 10 (wt %).
[0068] (Making terminal electrodes) A terminal electrode paste was applied to the end faces of the sintered body and thermally cured at 150° C. for 30 minutes to form a pair of terminal electrodes. In this way, an all-solid-state battery was completed.
[0069] (Evaluation of the average interplanar spacing d002 of carbon particles in the electrode active material layer) The electrode active material layer region of the obtained sintered body is exposed by polishing or the like and processed to be smooth. Using, for example, an X-ray diffraction apparatus (apparatus name: Xpert-N, manufactured by Malvem-Panalytical), the peak angle of the plane index (002) can be used to calculate 2d sinθ=n λ (where d is the plane spacing, θ is the measurement angle, n is an arbitrary integer, and λ is the wavelength of the X-rays used).
[0070] (Evaluation of the long side a and short side b of the carbon particles in the electrode active material) The electrode active material layer region of the obtained sintered body is exposed by polishing or the like and processed to be smooth, and from observation with a scanning electron microscope (SEM), the ratio a / b can be calculated for 100 or more carbon particles in the field of view, with the length in the longest axial direction of each carbon particle being a and the length in the shortest axial direction being b. An appropriate value for the magnification of the SEM is selected according to the particle size of the carbon particles, and a magnification is selected such that 100 to 300 particles are observed in the field of view. The a / b ratios of all carbon particles in the field of view are found and the average is calculated.
[0071] (Evaluation of particle size distribution of carbon particles in electrode active material) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth, and the area of each particle was measured by image processing for more than 200 particles in the field of view through scanning electron microscope (SEM) observation. The circle equivalent diameter was calculated from the area data, and the particle diameter at 10% by volume of the cumulative volume was defined as D10, and the particle diameter at 90% by volume of the cumulative volume was defined as D90.
[0072] (Evaluation of carbon content in electrode active material) The electrode active material layer of the obtained sintered body was separated and pulverized, and the carbon and sulfur were measured using a carbon / sulfur analyzer (manufactured by LECO Japan Co., Ltd., device name: CS-844) as the analytical device, using the oxygen flow combustion-infrared absorption method.
[0073] (Relative density measurement) The external dimensions of the obtained sintered body were measured, and the volume was calculated. The density of the sintered body was obtained by dividing the weight of the sintered body by the volume. On the other hand, the theoretical density in the shape and dimensions was obtained using the shape, dimensions and specific gravity of each component part of the sintered body. Specifically, in order to obtain the theoretical density, the dimensions of each component part of the sintered body were first calculated. Here, each component part of the sintered body is a part of the solid electrolyte layer, a part of the positive electrode active material layer, a part of the positive electrode current collector layer, a part of the negative electrode active material layer, and a part of the negative electrode current collector layer. Next, the volume of each component part was calculated from the shape and dimensions of each component part of the solid electrolyte layer. Next, the specific gravity of each component part of the solid electrolyte layer was multiplied by the calculated volume. The specific gravity of each component part was used as the specific gravity of each component part. Next, the weight of the sintered body was calculated by adding them up. In addition, the calculation was performed taking into account the abundance ratio for the positive electrode active material and the negative electrode active material having the active material and carbon. Next, the theoretical density was calculated by dividing the calculated weight of the sintered body by the volume of the sintered body. The relative density was then calculated by taking the ratio of the sintered density to the theoretical density. The relative density is calculated as (sintered density / theoretical density).
[0074] (Impedance evaluation) The obtained laminate was attached to a jig fixed with a spring pin and the internal resistance was measured using an Impedance / Gain-Phase analyzer (manufactured by Solartron Analytical, device name: 1260A). The measurement frequency was 0.005 Hz and the applied AC voltage was 0.05 V. The obtained internal resistance values are shown in Table 1. When the internal resistance value was 1×10 7 (Ω) or less was considered to be good.
[0075] (Evaluation of charge / discharge characteristics) The resulting laminate was then attached to a spring-loaded pin-fixed jig using a charge-discharge tester to measure the charge-discharge capacity. The measurement conditions were a current of 2μA during charging and discharging, and a voltage of 0V to 1.6V. The measured discharge capacity is shown in Table 1. A discharge characteristic value of more than 1.5μAh was considered good.
[0076] [Comparative Example 1] In this comparative example, a carbon material was used in which D10 was 0.25 μm, D90 was 4.5 μm, a / b was 3, and the average interplanar spacing d002 was 0.3425 (nm). The above-mentioned Li3V2(PO4)3 powder was used as the active material. The carbon material was weighed out to be 10 (wt%) relative to Li3V2(PO4)3 and mixed in an organic solvent using a ball mill. The powder was separated from the balls and organic solvent and dried to obtain a mixed powder of the carbon material and Li3V2(PO4)3. Furthermore, a laminate was produced using the same method as in Example 1, and then debindering and sintering were performed using the same method. The discharge characteristics of the laminate were evaluated using the same method as in Example 1. Table 1 shows the measured internal resistance values and discharge capacities.
[0077] As can be seen from Table 1, by using the carbon material and active material within the range of the present invention in the active material layer, even a small amount of addition can be effectively contained, thereby realizing a dense electrode portion, and it is clear that the internal resistance is low as an all-solid-state battery. It is also clear that a high discharge capacity is obtained.
[0078] [Table 1]
[0079] [Examples 5 to 12] (Mixing active material and carbon material) In order to demonstrate the effect of this embodiment, carbon materials having D10 of 0.25 μm and D90 of 4.5 μm, average interplanar spacing d002 of 0.33650.3380 (nm), and a / b of 1.0, 1.1, 1.5, 5.0, 10.0, 50.0, 100.0, and 200.0, respectively, were used as Examples 5 to 12. The active material used was the Li3V2(PO4)3 powder described above. These carbon materials were weighed out to be 11.3 wt% relative to Li3V2(PO4)3, and mixed in an organic solvent using a ball mill. The powder was separated from the balls and organic solvent and dried to obtain a mixed powder of the carbon material and Li3V2(PO4)3.
[0080] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive and negative electrode active material layers was prepared by adding 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent to 100 parts of a mixed powder of the above carbon material and Li3V2(PO4)3, and kneading and dispersing the mixture using a triple roll mill to prepare a paste for the active material layers that would become the positive and negative electrodes.
[0081] (Preparation of paste for solid electrolyte layer) The solid electrolyte is the above-mentioned Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was used. 100 parts of this powder were mixed with 100 parts of ethanol and 200 parts of toluene as solvents in a ball mill and wet-mixed. Then, 16 parts of polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare a paste for the solid electrolyte layer.
[0082] (Preparation of sheets for solid electrolyte layer) This paste for the solid electrolyte layer was formed into a sheet using a doctor blade method on a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.
[0083] (Preparation of Positive Electrode Current Collector Layer Paste and Negative Electrode Current Collector Layer Paste) Cu powder and Li3V2(PO4)3 powder were mixed in a weight ratio of 100:9, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added, and the mixture was mixed and dispersed using a triple roll to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.
[0084] (Preparation of terminal electrode paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting terminal electrode paste.
[0085] (Preparation of active material layer unit) On the above-mentioned solid electrolyte layer sheet, a paste for a positive electrode collector layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes. On top of that, a paste for a positive electrode active material layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes to form a positive electrode layer unit. On the other hand, a paste for a negative electrode active material layer was printed by screen printing to a thickness of 5 μm on the solid electrolyte layer sheet, and dried at 80° C. for 10 minutes, and then a paste for a negative electrode collector layer was printed by screen printing to a thickness of 5 μm on top of that, and dried at 80° C. for 10 minutes to form a negative electrode layer unit. Then, the PET film was peeled off.
[0086] (Preparation of Laminate) A single layer product was obtained by stacking the positive electrode layer unit, the negative electrode layer unit, and the solid electrolyte layer sheet in the order of the solid electrolyte layer, the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, the negative electrode current collector layer, and the solid electrolyte layer. At this time, each unit was stacked with a shift so that the positive electrode current collector layer of the positive electrode layer unit extended only to one end surface, and the negative electrode current collector layer of the negative electrode layer unit extended only to the other end surface. Then, this was molded by thermocompression bonding and cut to produce a laminate.
[0087] (Preparation of sintered body) The obtained laminate was debindered and then co-fired to obtain a sintered body. For debindering, the temperature was raised to 700°C at a rate of 50°C / hour in nitrogen and held at that temperature for 10 hours, and for co-firing, the temperature was raised to 850°C at a rate of 200°C / hour in nitrogen and held at that temperature for 1 hour, and then naturally cooled after firing. It was also confirmed that the residual carbon content in the electrode active material layer region of the obtained sintered body was approximately 10 (wt %).
[0088] (Making terminal electrodes) A terminal electrode paste was applied to the end faces of the sintered body and thermally cured at 150° C. for 30 minutes to form a pair of terminal electrodes. In this way, an all-solid-state battery was completed.
[0089] (Evaluation of the average interplanar spacing d002 of carbon particles in the electrode active material layer) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth. Using an X-ray diffractometer (device name: Xpert-N, manufactured by Malvem-Panalytical), the peak angle of the plane index (002) was used to calculate 2d sinθ=n λ (where d is the plane spacing, θ is the measurement angle, n is an arbitrary integer, and λ is the wavelength of the X-rays used).
[0090] (Evaluation of the long side a and short side b of the carbon particles in the electrode active material) The electrode active material layer region of the obtained sintered body is exposed by polishing or the like and processed to be smooth, and from observation with a scanning electron microscope (SEM), the length in the longest axial direction of 100 or more particles in the field of view is taken as a, the length in the shortest axial direction is taken as b, and the ratio of these can be calculated as a / b. An appropriate value for the magnification of the SEM is selected according to the particle size of the carbon particles, and a magnification is selected so that 100 to 300 particles are observed in the field of view. The a / b ratio of the carbon particles was calculated as the average a / b of all carbon particles in the field of view.
[0091] (Evaluation of particle size distribution of carbon particles in electrode active material) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth, and the area of each particle was measured by image processing for more than 200 particles in the field of view through scanning electron microscope (SEM) observation. The circle equivalent diameter was calculated from the area data, and the particle diameter at 10% by volume of the cumulative volume was defined as D10, and the particle diameter at 90% by volume of the cumulative volume was defined as D90.
[0092] (Evaluation of carbon content in electrode active material) The electrode active material layer of the obtained sintered body was separated and pulverized, and the carbon and sulfur were measured using a carbon / sulfur analyzer (manufactured by LECO Japan Co., Ltd., device name: CS-844) as the analytical device, using the oxygen flow combustion-infrared absorption method.
[0093] (Relative density measurement) The external dimensions of the obtained sintered body were measured, the volume was calculated, and the weight of the sintered body was divided by the volume to obtain the density of the sintered body. On the other hand, the theoretical density for the shape and dimensions was calculated, and then the ratio of the obtained density of the sintered body to the theoretical density was calculated to obtain the relative density.
[0094] (Impedance evaluation) The obtained laminate was attached to a jig fixed with a spring pin and the internal resistance was measured using an Impedance / Gain-Phase analyzer. The measurement frequency was 0.005 Hz and the applied AC voltage was 0.05 V. The obtained internal resistance values are shown in Table 2. When the internal resistance value was 1×10 7 (Ω) or less was considered to be good.
[0095] (Evaluation of charge / discharge characteristics) The resulting laminate was then attached to a spring-loaded pin-fixed jig using a charge-discharge tester to measure the charge-discharge capacity. The measurement conditions were a current of 2 μA during charge and discharge, and a voltage of 0 V to 1.6 V. Table 2 shows the measured discharge capacity.
[0096] As can be seen from Table 2, all-solid-state batteries using carbon materials having a / b in the range according to the present invention for the positive electrode active material layer and the negative electrode active material layer, respectively, clearly show low internal resistance. It is also clear that when the a / b value is in the range of 1.1 to 100.0, an even lower internal resistance is shown and good discharge capacity is obtained. It is also clear that when the a / b value is in the range of 1.5 to 5.0, an even lower internal resistance is shown and good discharge capacity is obtained.
[0097] [Table 2]
[0098] [Examples 13 to 15] (Mixing active material and carbon material) In order to demonstrate the effect of this embodiment, carbon materials having an average interplanar spacing d002 of 0.3365 (nm), a / b of 3.0, D10 of 0.1 μm and D90 of 5 μm (Example 13), D10 of 0.2 μm and D90 of 5.5 μm (Example 14), and D10 of 0.08 μm and D90 of 4.0 μm (Example 15) were used as Examples 13 to 15. In addition, the above-mentioned Li3V2(PO4)3 powder was used as the active material. These carbon materials were weighed to be 11.3 wt% relative to Li3V2(PO4)3, and mixed in an organic solvent using a ball mill. The powder was separated from the balls and organic solvent and dried to obtain a mixed powder of the carbon material and Li3V2(PO4)3.
[0099] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive and negative electrode active material layers was prepared by adding 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent to 100 parts of a mixed powder of the above carbon material and Li3V2(PO4)3, and kneading and dispersing the mixture using a triple roll mill to prepare a paste for the active material layers that would become the positive and negative electrodes.
[0100] (Preparation of paste for solid electrolyte layer) The solid electrolyte is the Li 1.3 Al0.3 Ti 1.7 (PO4)3 powder was used. 100 parts of this powder were mixed with 100 parts of ethanol and 200 parts of toluene as solvents in a ball mill and wet-mixed. Then, 16 parts of polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare a paste for the solid electrolyte layer.
[0101] (Preparation of sheets for solid electrolyte layer) This paste for the solid electrolyte layer was formed into a sheet using a doctor blade method on a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.
[0102] (Preparation of Positive Electrode Current Collector Layer Paste and Negative Electrode Current Collector Layer Paste) Cu powder and Li3V2(PO4)3 powder were mixed in a weight ratio of 100:9, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added, and the mixture was mixed and dispersed using a triple roll to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.
[0103] (Preparation of terminal electrode paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting terminal electrode paste.
[0104] (Preparation of active material layer unit) On the above-mentioned solid electrolyte layer sheet, a paste for a positive electrode collector layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes. On top of that, a paste for a positive electrode active material layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes to form a positive electrode layer unit. On the other hand, a paste for a negative electrode active material layer was printed by screen printing to a thickness of 5 μm on the solid electrolyte layer sheet, and dried at 80° C. for 10 minutes, and then a paste for a negative electrode collector layer was printed by screen printing to a thickness of 5 μm on top of that, and dried at 80° C. for 10 minutes to form a negative electrode layer unit. Then, the PET film was peeled off.
[0105] (Preparation of Laminate) A single layer product was obtained by stacking the positive electrode layer unit, the negative electrode layer unit, and the solid electrolyte layer sheet in the order of the solid electrolyte layer, the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, the negative electrode current collector layer, and the solid electrolyte layer. At this time, each unit was stacked with a shift so that the positive electrode current collector layer of the positive electrode layer unit extended only to one end surface, and the negative electrode current collector layer of the negative electrode layer unit extended only to the other end surface. Then, this was molded by thermocompression bonding and cut to produce a laminate.
[0106] (Preparation of sintered body) The obtained laminate was debindered and then co-fired to obtain a sintered body. For debindering, the temperature was raised to 700°C at a rate of 50°C / hour in nitrogen and held at that temperature for 10 hours, and for co-firing, the temperature was raised to 850°C at a rate of 200°C / hour in nitrogen and held at that temperature for 1 hour, and then naturally cooled after firing. It was also confirmed that the residual carbon content in the electrode active material layer region of the obtained sintered body was approximately 10 (wt %).
[0107] (Making terminal electrodes) A terminal electrode paste was applied to the end faces of the sintered body and thermally cured at 150° C. for 30 minutes to form a pair of terminal electrodes. In this way, an all-solid-state battery was completed.
[0108] (Evaluation of the average interplanar spacing d002 of carbon particles in the electrode active material layer) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth. Using an X-ray diffractometer (device name: Xpert-N, manufactured by Malvem-Panalytical), the peak angle of the plane index (002) was used to calculate 2d sinθ=n λ (where d is the plane spacing, θ is the measurement angle, n is an arbitrary integer, and λ is the wavelength of the X-rays used).
[0109] (Evaluation of the long side a and short side b of the carbon particles in the electrode active material) The electrode active material layer region of the obtained sintered body is exposed by polishing or the like and processed to be smooth, and from observation with a scanning electron microscope (SEM), the length in the longest axial direction of 100 or more particles in the field of view is taken as a, the length in the shortest axial direction is taken as b, and the ratio of these can be calculated as a / b. An appropriate value for the magnification of the SEM is selected according to the particle size of the carbon particles, and a magnification is selected so that 100 to 300 particles are observed in the field of view. The a / b of the carbon particles was calculated as the average a / b of all carbon particles in the field of view.
[0110] (Evaluation of particle size distribution of carbon particles in electrode active material) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth, and the area of each particle was measured by image processing for more than 200 particles in the field of view through scanning electron microscope (SEM) observation. The circle equivalent diameter was calculated from the area data, and the particle diameter at 10% by volume of the cumulative volume was defined as D10, and the particle diameter at 90% by volume of the cumulative volume was defined as D90.
[0111] (Evaluation of carbon content in electrode active material) The electrode active material layer of the obtained sintered body was separated and pulverized, and the carbon and sulfur were measured using a carbon / sulfur analyzer (manufactured by LECO Japan Co., Ltd., device name: CS-844) as the analytical device, using the oxygen flow combustion-infrared absorption method.
[0112] (Relative density measurement) The external dimensions of the obtained sintered body were measured, the volume was calculated, and the weight of the sintered body was divided by the volume to obtain the density of the sintered body. On the other hand, the theoretical density for the shape and dimensions was calculated, and then the ratio of the obtained density of the sintered body to the theoretical density was calculated to obtain the relative density.
[0113] (Impedance evaluation) The obtained laminate was attached to a jig fixed with a spring pin and the internal resistance was measured using an Impedance / Gain-Phase analyzer. The measurement frequency was 0.005 Hz and the applied AC voltage was 0.05 V. The obtained internal resistance values are shown in Table 3. When the internal resistance value was 1×10 7 (Ω) or less was considered to be good.
[0114] (Evaluation of charge / discharge characteristics) The resulting laminate was then attached to a spring-loaded pin-fixed jig using a charge-discharge tester to measure the charge-discharge capacity. The measurement conditions were a current of 2μA during charging and discharging, and a voltage of 0V to 1.6V. The measured discharge capacity is shown in Table 3. A discharge characteristic value of more than 1.5μAh was considered good.
[0115] As can be seen from Table 3, all-solid-state batteries using carbon materials having D10 and D90 within the ranges according to the present invention for the positive and negative electrode active material layers, respectively, clearly exhibit low internal resistance. In addition, it can be seen that batteries with D10 of 0.1 μm or more and D90 of 5.0 μm or less exhibit even lower internal resistance and have good discharge capacity.
[0116] [Table 3]
[0117] [Examples 16 to 21] (Mixing active material and carbon material) In order to demonstrate the effect of this embodiment, carbon materials having an average interplanar spacing d002 of 0.3380 (nm), a / b of 3, D10 of 0.25 μm, and D90 of 4.5 μm were used as Examples 16 to 21. The active material was the above-mentioned Li3V2(PO4)3 powder. These carbon materials were weighed out to be 0.49 wt%, 0.58 wt%, 1.13 wt%, 7.12 wt%, 11.30 wt%, and 16.95 wt% relative to Li3V2(PO4)3, respectively, and mixed in an organic solvent using a ball mill. The powder was separated from the balls and organic solvent and dried to obtain a mixed powder of the carbon material and Li3V2(PO4)3.
[0118] (Preparation of Positive Electrode Active Material Layer Paste and Negative Electrode Active Material Layer Paste) The paste for the positive and negative electrode active material layers was prepared by adding 15 parts of ethyl cellulose as a binder and 65 parts of dihydroterpineol as a solvent to 100 parts of a mixed powder of the above carbon material and Li3V2(PO4)3, and kneading and dispersing the mixture using a triple roll mill to prepare a paste for the active material layers that would become the positive and negative electrodes.
[0119] (Preparation of paste for solid electrolyte layer) The solid electrolyte is the Li 1.3 Al 0.3 Ti 1.7 (PO4)3 powder was used. 100 parts of this powder were mixed with 100 parts of ethanol and 200 parts of toluene as solvents in a ball mill and wet-mixed. Then, 16 parts of polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare a paste for the solid electrolyte layer.
[0120] (Preparation of sheets for solid electrolyte layer) This paste for the solid electrolyte layer was formed into a sheet using a doctor blade method on a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.
[0121] (Preparation of Positive Electrode Current Collector Layer Paste and Negative Electrode Current Collector Layer Paste) Cu powder and Li3V2(PO4)3 powder were mixed in a weight ratio of 100:9, and then 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent were added, and the mixture was mixed and dispersed using a triple roll to prepare a paste for a positive electrode current collector layer and a paste for a negative electrode current collector layer.
[0122] (Preparation of terminal electrode paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting terminal electrode paste.
[0123] (Preparation of active material layer unit) On the above-mentioned solid electrolyte layer sheet, a paste for a positive electrode collector layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes. On top of that, a paste for a positive electrode active material layer was printed by screen printing to a thickness of 5 μm, and dried at 80° C. for 10 minutes to form a positive electrode layer unit. On the other hand, a paste for a negative electrode active material layer was printed by screen printing to a thickness of 5 μm on the solid electrolyte layer sheet, and dried at 80° C. for 10 minutes, and then a paste for a negative electrode collector layer was printed by screen printing to a thickness of 5 μm on top of that, and dried at 80° C. for 10 minutes to form a negative electrode layer unit. Then, the PET film was peeled off.
[0124] (Preparation of Laminate) A single layer product was obtained by stacking the positive electrode layer unit, the negative electrode layer unit, and the solid electrolyte layer sheet in the order of the solid electrolyte layer, the positive electrode current collector layer, the positive electrode active material layer, the solid electrolyte layer, the negative electrode active material layer, the negative electrode current collector layer, and the solid electrolyte layer. At this time, each unit was stacked with a shift so that the positive electrode current collector layer of the positive electrode layer unit extended only to one end surface, and the negative electrode current collector layer of the negative electrode layer unit extended only to the other end surface. Then, this was molded by thermocompression bonding and cut to produce a laminate.
[0125] (Preparation of sintered body) The obtained laminate was debindered and then co-fired to obtain a sintered body. For debindering, the temperature was raised to 700°C at a rate of 50°C / hour in nitrogen and held at that temperature for 10 hours, and for co-firing, the temperature was raised to 850°C at a rate of 200°C / hour in nitrogen and held at that temperature for 1 hour, and then naturally cooled after firing. It was also confirmed that the residual carbon contents in the electrode active material layer region of the obtained sintered bodies were 0.43, 0.51, 1.00, 6.30, 15.00, and 16.00 (wt %), respectively.
[0126] (Making terminal electrodes) A terminal electrode paste was applied to the end faces of the sintered body and thermally cured at 150° C. for 30 minutes to form a pair of terminal electrodes. In this way, an all-solid-state battery was completed.
[0127] (Evaluation of the average interplanar spacing d002 of carbon particles in the electrode active material layer) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth. Using an X-ray diffraction apparatus (apparatus name: Xpert-N, manufactured by Malvem-Panalytical), the peak angle of the plane index (002) was calculated from the Bragg equation 2d sinθ=n λ (where d is the plane spacing, θ is the measurement angle, n is an arbitrary integer, and λ is the wavelength of the X-rays used).
[0128] (Evaluation of the long side a and short side b of the carbon particles in the electrode active material) The electrode active material layer region of the obtained sintered body is exposed by polishing or the like and processed to be smooth, and from observation with a scanning electron microscope (SEM), the length in the longest axial direction of 100 or more particles in the field of view is taken as a, the length in the shortest axial direction is taken as b, and the ratio of these can be calculated as a / b. An appropriate value for the magnification of the SEM is selected according to the particle size of the carbon particles, and a magnification is selected so that 100 to 300 particles are observed in the field of view. The a / b ratio of the carbon particles was calculated as the average a / b of all carbon particles in the field of view.
[0129] (Evaluation of particle size distribution of carbon particles in electrode active material) The electrode active material layer region of the obtained sintered body was exposed by polishing or the like and processed to be smooth, and the area of each particle was measured by image processing for more than 200 particles in the field of view through scanning electron microscope (SEM) observation. The circle equivalent diameter was calculated from the area data, and the particle diameter at 10% by volume of the cumulative volume was defined as D10, and the particle diameter at 90% by volume of the cumulative volume was defined as D90.
[0130] (Evaluation of carbon content in electrode active material) The electrode active material layer of the obtained sintered body was separated and pulverized, and the carbon and sulfur were measured using a carbon / sulfur analyzer (manufactured by LECO Japan Co., Ltd., device name: CS-844) as the analytical device by the oxygen flow combustion-infrared absorption method.
[0131] (Relative density measurement) The external dimensions of the obtained sintered body were measured, the volume was calculated, and the weight of the sintered body was divided by the volume to obtain the sintered body density. Meanwhile, the theoretical density for the shape and dimensions was calculated, and then the ratio of the obtained sintered body density to the theoretical density was obtained to obtain the relative density. The relative density is obtained by (sintered body density / theoretical density).
[0132] (Impedance evaluation) The obtained laminate was attached to a jig fixed with a spring pin and the internal resistance was measured using an Impedance / Gain-Phase analyzer. The measurement frequency was 0.005 Hz and the applied AC voltage was 0.05 V. The obtained internal resistance values are shown in Table 4. When the internal resistance value was 1×10 7 (Ω) or less was considered to be good.
[0133] (Evaluation of charge / discharge characteristics) The resulting laminate was then attached to a spring-loaded pin-fixed jig using a charge / discharge tester to measure the charge / discharge capacity. The measurement conditions were a current of 2μA during charging and discharging, and a voltage of 0V to 1.6V. The measured discharge capacity is shown in Table 4. A discharge characteristic value of more than 1.5μAh was considered good.
[0134] As can be seen from Table 4, all-solid-state batteries using carbon materials with contents within the range of the present invention in the positive and negative active material layers clearly have dense sintered bodies and exhibit low internal resistance. It can also be seen that when the carbon particle content is 0.5 (wt%) or more and 15.0 (wt%) or less, a good discharge capacity is obtained while exhibiting even lower internal resistance. It can also be seen that when the carbon particle content is 1.00 (wt%) or more and 15.0 (wt%) or less, a good discharge capacity is obtained while exhibiting even lower internal resistance.
[0135] [Table 4]
[0136] As described above, the all-solid-state battery according to the present invention is effective in reducing the internal resistance. [Explanation of symbols]
[0137] 1 Positive electrode layer 2. Negative electrode layer 3 Solid electrolyte layer 4. Laminate 5, 6 terminal electrode 10 All-solid-state battery
Claims
1. a positive electrode layer including a positive electrode current collector layer and a positive electrode active material layer, and a negative electrode layer including a negative electrode current collector layer and a negative electrode active material layer; a solid electrolyte layer including a solid electrolyte; the positive electrode active material layer and the negative electrode active material layer each contain carbon particles having an average interplanar spacing d002 of less than 0.342 (nm), The all-solid-state battery, wherein in the particle size distribution of the carbon particles, D10 is 0.1 μm or more and D90 is 5.0 μm or less.
2. 2. The all-solid-state battery according to claim 1, wherein the ratio of a long side of the carbon particle to a short side of the carbon particle is 1.0<a / b.
3. 3. The all-solid-state battery according to claim 1, wherein the positive electrode active material layer and the negative electrode active material layer each contain 0.5 (wt %) or more and 15.0 (wt %) or less of the carbon particles.
Citation Information
Patent Citations
Fluorine-containing elastomer coating wire
JP1983004208A
Si / C electroactive material composition
JP2015510666A
All-solid type secondary battery
JP2018170189A